1989
DOI: 10.1111/j.1460-2466.1989.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Computers for Political Change: PeaceNet and Public Data Access

Abstract: By “constructing an alternative public realm,” two computer communication projects—one devoted to pace issues, the other to making U.S. government information more broadly available—demonstrate the potential of new technology for grass‐roots political movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 7 publications
0
24
0
4
Order By: Relevance
“…Downing noted a tension between "Stalinistic centralism" and populism in his study of network-based peace organizations. He noted that the groups occasionally had to restrain discussion even though they preferred to make decisions by consensus [5]. Abrahamson et al noted similar problems with two way television [1].…”
Section: Discussionmentioning
confidence: 98%
“…Downing noted a tension between "Stalinistic centralism" and populism in his study of network-based peace organizations. He noted that the groups occasionally had to restrain discussion even though they preferred to make decisions by consensus [5]. Abrahamson et al noted similar problems with two way television [1].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, some studies have found that new communities were formed on the Internet in social movement campaigns, and seem to support the view that computer networking helps identity building. Downing (1989), studying PeaceNet, found that computer networks, apart from serving information and coordination functions, act as forums for developing agendas for political action. Price (1998) reported that, in the campaign against anti-personnel landmines, the network on the Internet created a space for virtual communities to debate politics, on top of breaking open access to the policy process and creating communities of experts outside of government.…”
Section: Use Of the Internet By Social Movementsmentioning
confidence: 99%
“…For all-sized nonprofits, the high cost of accessing many public databases has long been a substantial obstacle to utilizing new information and communications technologies (Downing 1989), and can further widen the gap between "haves" and "have-nots" nonprofits. 5 Norheim (2004, p. 45) found that, relative to the well funded U.S. Forest Service, funding constrained what data could be purchased and at what resolution by the nonprofit Wilderness Society and, consequently, affected how the area could be analyzed.…”
Section: Economics Of Data Accessmentioning
confidence: 99%